Using Personal Rapid Transit as an Effective Transport Solution in Historical Downtown Areas: a Case From Historic Kemeraltı, İzmir - Duvarcı, Yavuz; Akpınar, Figen; Akpınar, Figen; Duvarcı, Yavuz (TMMOB Şehir Plancıları Odası, 2023)
Many issues related to the conservation of urban heritage are closely related to the transit system and the use of private trans-portation. Regeneration, revitalization, and/or heritage conser-vation are not properly managed due to problems arising directly from inconvenient transport solutions that cannot provide or resolve the accessibility and mobility needs of vulnerable groups together with inappropriate space management while indirectly causing economic shrinkage and loss of vitality. Furthermore, even if modern modes of transportation are used, they will cause significant environmental and societal difficulties, making them unsuitable for such sensitive places. This article, using a micro -simulation approach, investigates whether a Personal Rapid Tran-sit system is physically applicable, and whether it can meet exist-ing travel requirements to prove that it is sufficient for the needs of local level mobility, and finally whether other environmental/ social impacts such that land use, air pollution, safety, sustainabil-ity are positive or negative. As a method, these outputs of the system application are presented as validations of the usefulness of the PRT. Finally, it was found that there is a gain in productiv-ity in terms of mobility as well as other socio-economic benefits besides the physical applicability of the method. The study's goal is to get the information out about how PRT technology may help produce more ecologically friendly and sustainable solutions while also conserving historical assets.
Tarihi kent merkezlerinde bireysel hızlı toplu taşımanın etkin bir ulaşım çözümü olarak kullanımı: İzmir tarihi Kemeraltı örneği
Keywords: Personal rapid transit; Smart transportation; Sustainable transportation policy; Travel